Optical coherence tomography to detect acute esophageal radiation‐induced damage in mice: A validation study. Issue 9 (26th June 2019) - Jelvehgaran, Pouya; de Bruin, Daniel M.; Khmelinskii, Artem; Borst, Gerben; Steinberg, Jeffrey D.; Song, Ji‐Ying; de Vos, Judith; van Leeuwen, Ton G.; Alderliesten, Tanja; de Boer, Johannes F.; van Herk, Marcel
Abstract: Radiation therapy for patients with non‐small‐cell lung cancer is hampered by acute radiation‐induced toxicity in the esophagus. This study aims to validate that optical coherence tomography (OCT), a minimally invasive imaging technique with high resolution ( 10 μm), is able to visualize and monitor acute radiation‐induced esophageal damage (ARIED) in mice. We compare our findings with histopathology as the gold standard. Irradiated mice receive a single dose of 40 Gy at proximal and distal spots of the esophagus of 10.0 mm in diameter. We scan mice using OCT at two, three, and seven days post‐irradiation. In OCT analysis, we define ARIED as a presence of distorted esophageal layering, change in backscattering signal properties, or change in the esophageal wall thickness. The average esophageal wall thickness is 0.53 mm larger on OCT when ARIED is present based on histopathology. The overall sensitivity and specificity of OCT to detect ARIED compared to histopathology are 94% and 47%, respectively. However, the overall sensitivity of OCT to assess ARIED is 100% seven days post‐irradiation. We validate the capability of OCT to detect ARIED induced by high doses in mice. Nevertheless, clinical studies are required to assess the potential role of OCT to visualize ARIED in humans. Abstract : Radiation therapy for patients with non‐small‐cell lung cancer is hampered by acute radiation‐induced toxicity in the esophagus. This study aims to validate that optical coherence tomography, a minimally invasive imaging technique with high resolution, is able to visualize and monitor acute radiation‐induced esophageal damage in mice. The findings are compared with histopathology as the gold standard.